Multiplicity of Solutions for a Class of Nonlinear Fractional Boundary Value Systems via Variational Approach - Kamache, Fares; Guefaifia, Rafik; Boulaaras, Salah (Journal of Applied Nonlinear Dynamics, 2026)
In this work, it is proved the existence of at least three weak solutions can be obtained for a new class of nonlinear fractional boundary value systems by using variational methods combined with a critical point theory due to Bonano and Marano while two examples in $% %TCIMACRO{\U{211d} }% %BeginExpansion \mathbb{R} %EndExpansion ^{3}$ and $% %TCIMACRO{\U{211d} }% %BeginExpansion \mathbb{R} %EndExpansion ^{4}$ are given to illustrate our main results applications.